Das dunkle Kochbuch einer Heldin. Janas Mutterfiguren in Adresát Milena Jesenská und Hrdinství je povinné - Matteo Colombi (Slovo a Smysl, 2017)
The article deals with two prominent representations of the mother in Jana Krejcarová’s written production: first Milena Jesenská’s portrait in Jana’s biography of her mother, Adresát Milena Jesenská [Addressee Milena Jesenská] (1969) — and secondly the character of Petr’s mother in the short novel Hrdinství je povinné [Heroism is compulsory] (1964), a fictional story with an apparent autobiographic background. The study shows that both representations are based on the child’s ambivalent attitude toward its mother: the analysis works on the hypothesis that the topic of social engagement is in both texts at the very core of this ambivalence. Public commitment is both for Jana as a biographer and for her fictional character Petr a reason for admiring the mother on the one hand and a great emotional and ethic challenge on the other hand — for the child is jealous of the mother’s social engagement and considers it as the very force not only keeping her away from him but also causing, eventually, her death. Moreover, the child feels split, becoming an adult, between the perspective to be as socially engaged, or even heroic, as the mother — and the refusal of a behaviour that seems to give priority to the social rather than to private sphere. Indeed, this ambivalence in the child-mother-relationship brands a depiction of the mother which is as subtly nuanced as emotionally and ethically demanding.